Find the AP if the first three terms of the AP are 2a + 1, a2 + a + 1 and 3a square ? 3a + 3 .

Asked by  | 8th Feb, 2012, 08:15: PM

Expert Answer:

Since the common difference is same
So
2nd term - 1st term = 3rd term - 2nd term
a2 - a  =  2a2 + 2a + 2
So,
a2 + 3a + 2 = 0
(a+1)(a+2) = 0
a = -1 , -2
A.P. :  -1 , 1 , 3 ....... OR  -3 , 3 , 9 .......

Answered by  | 9th Feb, 2012, 10:32: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.